La comunidad moral entre las mujeres musulmanas ceutíes: de mecanismo de cohesión social a mecanismo de control - Cubo Barea, Francisco (CUADERNOS KÓRE, 2012)
The moral community is a conceptual construct through which we represent the complex structure that is formed by the Muslim women in Ceuta (and also in nearby Morocco). Its aim is to reproduce the cultural model of their community by means of efficient mechanisms of social control. If in the past it has made the cohesion of the group, regarding traditional cultural norms possible, then actually its function seems to have been altered substantially because of the interference of the male in the subtle forms of interaction that used to belong exclusively to the femenine domain. Although we ignore the reason for this interference, everything points to the rapid process of Islamization that exists in the town.